Between Modes and Keys: German Theory 1592-1802 - Lester, Joel (Stuyvesant, NY Pendragon, 1990)
This study of music theory examines in detail the persistence of modal thinking in German-speaking areas, which coexisted with major-minor principles, and its impact on German music from the Baroque through the High Classical period.
Keywords: 16th Century (1501-1600); 17th Century (1601-1700); 18th Century (1701-1800); Harmony; Music theory; Germany